Suicide dan Medikasi: Studi Kepada Remaja Broken Home di Desa Parbuluan III - Sempurna Sihombing (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This research aims to provide guidance and guidance for counselors in assisting teenagers who intend to commit suicide, both in cases of broken homes and other cases. The focus of the research is suicide experienced by a teenager in a broken home case in Parbuluan III village. This research uses a qualitative method with a case study method for teenagers from broken homes who intend to commit suicide. Data collection was carried out through interviews with the three teenagers, the teenagers' families and friends of the teenagers, observation of data sources and documentation. The problems experienced are teenagers with broken homes, including parents who are divorced/separated, one parent dies, experiencing physical violence from a single parent mother and parents who are separated, giving up responsibility for the teenager's life. Cases of broken homes in teenagers give rise to suicidal intentions which are caused by several factors, namely family factors, social factors, economic factors, psychological factors and spiritual factors. That is why this case resulted in sad and angry emotions in teenagers who intended to commit suicide. In this case, it was carried out using medication, namely behavioral dialectical therapy using an emotional regulation module. The techniques used through emotional regulation are understanding and naming emotions, reducing the frequency of unwanted emotions to stop them and changing unwanted emotions, increasing resilience by managing positive emotional thoughts and reducing emotional suffering, namely managing emotions so as not to make the situation worse when emotional. painful to control someone. This research provides an understanding ofhow medication can prevent the suicidal intentions of broken home teenagers with behavioral dialectical therapy so that it produces a positive impact, namely self-acceptance of a new family, teenagers are more confident and committed to living a better life.